2018
DOI: 10.1007/s11136-018-1986-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) in beta-thalassemia major (β-TM) patients assessed by 36-item short form health survey (SF-36): a meta-analysis

Abstract: BTM could adversely affect the HRQoL of patients. Measuring HRQoL should be considered as an essential part of the overall assessment of health status of BTM patients, which would provide valuable clues for improving the management of disease and making decisions on the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 43 publications
3
51
1
1
Order By: Relevance
“…As expected and reported before [20,31,32], our results show that higher pretransfusion haemoglobin levels and lower hepatic and splenic sizes are associated with better HRQoL scores. Similarly, longer duration of hospital stay for transfusion and increasing distance to travel from home to hospital were both correlated with lower HRQoL scores.…”
Section: Discussionsupporting
confidence: 91%
“…As expected and reported before [20,31,32], our results show that higher pretransfusion haemoglobin levels and lower hepatic and splenic sizes are associated with better HRQoL scores. Similarly, longer duration of hospital stay for transfusion and increasing distance to travel from home to hospital were both correlated with lower HRQoL scores.…”
Section: Discussionsupporting
confidence: 91%
“…HRQoL surveys of children with TDT have been carried out in Malaysia [7][8][9], Thailand [10][11][12], India [13][14][15] and the Middle East [16][17][18][19][20]. Although the principles of treatment are similar, HRQoL outcomes are heavily influenced by experiences, beliefs, expectations, cultural differences and access to health care [21], justifying the need for local studies.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 26 studies in which thalassemic children were targeted concluded that thalassemia adversely affects health-related quality of life of these children. Furthermore, quality of life should be considered as an essential part of overall health assessment of these patients [18] .…”
Section: Discussionmentioning
confidence: 99%